Productive efficiency in the iron and steel sector under state planning : The case of China and former Czechoslovakia in a comparative perspective - Nielsen, Hana (Applied Energy, 2017)
State-ownership has often been discussed as one of the major causes of poor industrial energy efficiency performance. This paper utilizes long-run historical data on the energy and material use in one specific industrial sector – the iron and steel production – in countries with both central-planning and market-based system, with a particular focus on former Czechoslovakia paralleled with the developments in China. Czechoslovak productive efficiency of the iron and steel sector fluctuated below the energy efficiency frontier. Until the early 1970s, the country's iron sector was one of the least efficient ones in our sample. It was, however, during the decades of 1970s and 1980s that efficiency measures were adopted and the energy efficiency of the Czechoslovak iron and steel sector increased significantly to, despite of a priori expectations, reach the energy efficiency frontier. Empirical results for other planned economies show similar development of catching-up to the market economies, particularly in the iron production sector during 1980s. A pattern of efficiency convergence was identified. In China, despite its move toward more market oriented economy, the productive efficiency lagged behind as recently as in 2000 (20–35 percent below the efficiency frontier). The relatively late adoption of energy conservation programs and the persistent government control of the sector in certain provinces slowed down the efficiency improvements. In the socialist economies of Eastern Europe, though, central-planners were able to achieve satisfactory productivity increases, primarily driven by efficiency and saving policies and adjustments in existing technology. It is likely, that as was the case of Eastern Europe, the adoption of vigorous energy policies with clearly defined targets accompanied by monitoring and supervision, will have a tremendous impact on the energy intensity as well as the absolute energy use of the sector in China.
Keywords: Energy efficiency; Productivity; Central planning; Steel industry; Data envelopment analysis